The amateur [videorecording (Blu-Ray)] - Nolan, Ken; Spinelli, Gary; Malek, Rami; Brosnahan, Rachel; Balfe, Caitríona; Stuhlbarg, Michael; McCallany, Holt; Nicholson, Julianne, 1971-; Fishburne, Laurence, III, 1961-; Bernthal, Jon; Littell, Robert, 1935- (20th Century Studios, 2025)
Charlie Heller is a brilliant, but deeply introverted decoder for the CIA working out of a basement office at headquarters in Langley whose life is turned upside down when his wife is killed in a London terrorist attack. When his supervisors refuse to act, he takes matters into his own hands, embarking on a dangerous trek across the globe to track down those responsible, his intelligence serving as the ultimate weapon for eluding his pursuers and achieving his revenge.